2002
DOI: 10.1038/sj.bmt.1703761
|View full text |Cite
|
Sign up to set email alerts
|

W/Wv marrow stromal cells engraft and enhance early erythropoietic progenitors in unconditioned Sl/Sld murine recipients

Abstract: Our data suggest that in this murine model, splenic erythropoiesis may influence stromal cell therapy, and that higher levels of marrow engraftment may be necessary to obtain a clinically significant effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, Bubnic et al demonstrated that W/Wv mouse - derived marrow stromal cells engrafted into the marrow compartment and enhanced early erythropoiesis in unconditioned Sl/Sld murine recipients. Engraftment of donor stromal cells reached levels of up to 1.0% of total marrow cells 4 months post transplantation 52 . This report was interesting because transplanted MSC do not usually replace the endogenous microenvironment, even after conditioning.…”
Section: Systemic Cytokine Production From Genetically Engineered mentioning
confidence: 98%
“…However, Bubnic et al demonstrated that W/Wv mouse - derived marrow stromal cells engrafted into the marrow compartment and enhanced early erythropoiesis in unconditioned Sl/Sld murine recipients. Engraftment of donor stromal cells reached levels of up to 1.0% of total marrow cells 4 months post transplantation 52 . This report was interesting because transplanted MSC do not usually replace the endogenous microenvironment, even after conditioning.…”
Section: Systemic Cytokine Production From Genetically Engineered mentioning
confidence: 98%
“…These MSCs were cultured in long-term marrow culture medium according to our previously described method [26]. Briefly, 4 -5 ϫ 10 7 MSCs per mouse were collected and cultured using a long-term marrow culture medium consisting of 12.5% fetal bovine serum, 12.5% horse serum, 1% antibiotic-antimycotic solution, 1% glutamine, 1% vitamin solution, 0.8% essential amino acid, 0.4% nonessential amino acid, 1% sodium pyruvate, 1% sodium bicarbonate solution, 0.036% hydrocortisone (Sigma-Aldrich, St. Louis, http://www.sigmaaldrich.…”
Section: Bone Marrow-derived Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…Both mKitL and sKitL may bind c-kit; however, the signaling mechanism differs. For instance, the Steel-Dickie mouse, which is deficient in mKitL, has a defect in the hematopoietic supportive microenvironment within the bone marrow despite physiological levels of sKitL and is unable to accept bone marrow transplantation (29). Cleavage of mKitL to sKitL may occur by proteolytic enzymes (30).…”
mentioning
confidence: 99%